LEGAL CONSEQUENCES OF THE DEATH OF AN EMPLOYEE - Antić, Aleksandar (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
An employment relationship is a legal relationship, which, like any other legal relationship, ceases to produce its legal consequences in the case of the termination of the existence of one of the contracting parties. The employment contract does not have legal consequences if the employer ceases to exist, through bankruptcy or liquidation, but also in the event of the employee's death.Upon a natural person's death, his rights and obligations cease and are transferred to his heirs. However, not all rights of a natural person are inheritable, only those that have a property law character, while those that were related to the personality of the deceased are not inherited.In the event of the death of an employee, the question arises, which rights the employee had can be inherited and which cannot, that is, which are of a property law nature, and which are related to the personality of the employee and therefore cannot be inherited.The death of the employee leads to the termination of the employment relationship, regardless of the will of the employer, i.e. „by force of law“, but it also produces other consequences for the employer, considering that he has certain financial obligations towards the family of the deceased employee, and also towards the deceased employee because he is obliged to pay all the income that the employee earned until his death. After the initiation of probate proceedings, the sums paid by the employer to the deceased employee's account enter the probate estate and become the subject of inheritance.Family members exercise the rights they have towards the employer based on the death of the employee directly with the employer. By these rights, we mean compensation for the costs of funeral services and possibly the right to joint assistance, if it is provided for by the general act of the employer or the employment contract, given that the same is not established by the Labor Law. One of the open questions is whether family members can claim rights from the employer, i.e. whether they submit the request for rights individually or jointly.Also, if the employee's death occurred as a result of an injury at work or an occupational disease, the family members of the deceased employee would have the right to claim compensation from the employer.The Labor Law does not regulate in detail the consequences that occur in the event of the death of an employee, except for the right to compensation for the costs of funeral services that the family members of the deceased have. However, with special collective agreements, the rights of family members are much more precisely regulated.To resolve other open issues, which are related to the consequences that occur in the event of the death of an employee, it is necessary to apply the rules of inheritance law, considering that in this case, it is a border area between inheritance and employment law.
Keywords: termination of employment due to the death of the employee; consequences of the death of the employee; compensation for the cost of funeral services; rights that can be inherited and rights that cannot be inherited; probate proceedings